LA TECNOLOGIA A NEUTRALIZZAZIONE DI CARICA PER LA DEUMIDIFICAZIONE DELLE MURATURE SOGGETTE A RISALITA CAPILLARE - Mauri, Davide (Archeomatica, 2013)
In view of the electrically operated systems on the market, the Tncstands in absolute as the fi rst and only "system to neutralize electro-charge" for its unique and exclusive "active principle" that characterizesthe technology developed by Leonardo Solutions Group-Domodry.